2017
DOI: 10.9767/bcrec.13.1.1222.97-112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying Conditions on the Catalytic Performance, Structure, and Reaction Rates over the Fe-Co-Mn/MgO Catalyst for Production of Light Olefins

Abstract: The MgO-supported Fe-Co-Mn catalysts, prepared using co-precipitation procedure, were tested for production of light olefins via CO hydrogenation reaction. The effect of a range of drying conditions including drying temperature and drying time on the structure and catalytic performance of Fe-Co-Mn/MgO catalyst for Fischer-Tropsch synthesis was investigated in a fixed bed micro-reactor under the same operational conditions of T = 350 °C, P = 1 bar, H2/CO = 2/1, and GHSV = 4500 h -1 . It was found that the catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In order to use the equation of a plug reactor for the calculation the rate of CO consumption in a differential reactor, the equation wileyonlinelibrary.com/jctb was changed, as explained in our previous works. [32][33][34][35][36] Finally Eqn (4) was obtained:…”
Section: Catalyst Evaluation Systemmentioning
confidence: 99%
“…In order to use the equation of a plug reactor for the calculation the rate of CO consumption in a differential reactor, the equation wileyonlinelibrary.com/jctb was changed, as explained in our previous works. [32][33][34][35][36] Finally Eqn (4) was obtained:…”
Section: Catalyst Evaluation Systemmentioning
confidence: 99%
“…Drying has a direct effect on the reactant's diffusion and many factors can influence the morphology of the synthesis gel including temperature, aging time, synthesis gel composition, and structure-directing agent [6]. One of the most important steps in catalyst preparation using precipitation methods is drying the obtained precipitate and the drying method affects the final catalyst's structure, texture, porosity, surface area, and morphology [7]. Washing silica gels which were produced using tetraethylorthosilicate (TEOS) and ammonium hydroxide (NH4OH) with various aprotic solvents show that the pore volume increased [8].…”
Section: Introductionmentioning
confidence: 99%
“…18 In our previous works the effect of different preparation and operational parameters on the catalytic performance of Fe-Co-Mn/MgO catalyst and also kinetic of CO hydrogenation reaction over these catalysts were investigated. [19][20][21][22][23][24][25] It was found that the catalytic performance and structural characteristics of the catalysts were strongly affected by these conditions. It was also found that the kinetic and mechanism of the CO hydrogenation reaction depend obviously on the catalyst preparation method.…”
Section: Introductionmentioning
confidence: 99%